Integrative Production Technology Theory and Applications - Brecher, Christian; Özdemir, Denis; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This contributed volume contains the research results of the Cluster of Excellence "Integrative Production Technology for High-Wage Countries", funded by the German Research Society (DFG). The approach to the topic is genuinely interdisciplinary, covering insights from fields such as engineering, material sciences, economics and social sciences. The book contains coherent deterministic models for integrative product creation chains as well as harmonized cybernetic models of production systems. The content is structured into five sections: Integrative Production Technology, Individualized Production, Virtual Production Systems, Integrated Technologies, Self-Optimizing Production Systems and Collaboration Productivity.The target audience primarily comprises research experts and practitioners in the field of production engineering, but the book may also be beneficial for graduate students. .
Overview -- Integrative Production Technology - Theory of Production and Applications -- Direct, Mold-less Production Systems -- Mold-based Production Systems -- Virtual Production Intelligence -- Integrated Computational Materials and Production Engineering -- Multi-Technology Platforms -- Multi-Technology Products -- Cognition-enhanced, Self-optimizing Production Networks -- Self-optimizing Production Technologies -- Cognition-Enhanced, Self-optimizing Assembly Systems -- Scientific Cooperation Engineering -- Towards a Technology-oriented Theory of Production -- Technology Platforms. .
Keywords: Industrial Management; Manufactures; Production management; Mathematical optimization; Operations research; Management science; Industrial Management; Machines, Tools, Processes; Operations Management; Continuous Optimization; Operations Research, Management Science